End of the Line for the Local Loop Monopoly? Technology, Competition, and Investment in Telecom Networks - Smith, Peter (World Bank, Washington, DC, 2012)
Local telephone service is the last bastion of a still frequently asserted public policy preference for monopoly provision of telecommunications. This Note challenges the rationale for that preference, addressing four issues: First, is local network competition feasible from a technical and cost point of view? Second, is telecommunications competition accepted by major investors? Third, how important is competition from a public policy point of view? And fourth, how can it be made to work? This Note makes the case that local network competition is increasingly feasible from a technical and cost point of view, that it is increasingly accepted by investors, and that it offers important benefits from a public policy point of view. But in order to work, it must be supported by effective regulation. Policymakers should be encouraged to address the critical issues of this transition toward a competitive telecommunications sector.